Taxonomic notes on Australian herbivorous ladybird beetles (Coccinellidae: Epilachnini) - Szawaryn, Karol (Zootaxa, 2018)
The Australian fauna of ladybird beetles (Coccinellidae) is very diverse and estimated to include about 500 species with only 260 species currently described (Ślipiński 2007). The tribe Epilachnini is poorly represented and consists of only ten species (Li 1993, Ślipiński 2007). Most of them are widely distributed in Asia and Oceania except Epilachna dawkinsi Li, 1993. This species was originally described by Li (1993) from South Australia near Adelaide, from a single female specimen. There were efforts made to collect other specimens of this beetle but they were not successful. Li drew the female genitalia (precisely one female coxite) but they did not resemble the genitalia of any Australian or Asian members of Epilachnini.